2017
DOI: 10.1111/iej.12778
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ knowledge regarding the indications for antibiotics in the management of endodontic infections

Abstract: Mart ın-Jim enez M, Mart ın-Biedma B, L opez-L opez J, Alonso-Ezpeleta O, Velasco-Ortega E, Jim enez-S anchez MC, Segura-Egea JJ. Dental students' knowledge regarding the indications for antibiotics in the management of endodontic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
5
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(94 citation statements)
references
References 47 publications
14
69
5
6
Order By: Relevance
“…, ESE ), high numbers of G1 participants believed that an acute apical abscess was an indication for antibiotics prescription (Q.4 II), the trend to overuse antibiotics in this situation was in agreement with Martín‐Jiménez et al . () who reported that the vast majority of final year students would prescribe antibiotics when a swelling was present. Therefore, one could speculate that those students after qualification could contribute to the unnecessary prescribing of antibiotics for such condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, ESE ), high numbers of G1 participants believed that an acute apical abscess was an indication for antibiotics prescription (Q.4 II), the trend to overuse antibiotics in this situation was in agreement with Martín‐Jiménez et al . () who reported that the vast majority of final year students would prescribe antibiotics when a swelling was present. Therefore, one could speculate that those students after qualification could contribute to the unnecessary prescribing of antibiotics for such condition.…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothetical case scenarios, it was noticeable that the majority of the final year students would prescribe antibiotics to treat teeth with necrotic pulp tissues and symptomatic apical periodontitis (75%), similarly Martín‐Jiménez et al . () reported that 44% of final year students in Spain would also prescribe antibiotics to treat this condition. The number of students who would misuse antibiotics to treat irreversible pulpitis (Q.10) was much lower (25%) in the present study compared to those reported by Martín‐Jiménez et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in four universities in Spain (Barcelona, Seville, Santiago de Compostela and Zaragoza) (Martín‐Jiménez et al . ) concluded that whilst the majority of students were aware of the correct management of endodontic infections, others still displayed an inappropriate use of antibiotics. Of particular note was the proposed use of antibiotics in certain situations such as irreversible pulpitis, apical periodontitis, and use of antibiotic therapy for longer than 7 days.…”
Section: Introductionmentioning
confidence: 99%